A Fluorescent Sensor Array Based on Heteroatomic Macrocyclic Fluorophores for the Detection of Polluting Species in Natural Water Samples - Lvova, Larisa; Caroleo, Fabrizio; Garau, Alessandra; Lippolis, Vito; Giorgi, Luca; Fusi, Vieri; Zaccheroni, Nelsi; Lombardo, Marco; Prodi, Luca; Di Natale, Corrado; Paolesse, Roberto (Frontiers in Chemistry, 2018)
The development of a novel all-solid-state optical sensor array based on heteroatomic macrocyclic fluorophores (diaza-crown ether, metallocorrole and pyridinophans) for the photographic analysis of liquid media, is presented. The sensitivity of the new optical system toward a number of different species (cations: Li+, K+, Na+, NH4+, Mg2+, Ca2+, Co2+, Cu2+, Zn2+, Cd2+,Pb2+ and anions: NO2, NO3, Cl, Br, HCO3) was evaluated both in single selective sensor mode and in multisensory arrangement. The satisfactory PLS1 regression models between sensor array optical response and analyte concentration were obtained for Cd2+, Cu2+, Zn2+ and NO2 ions in all the range of tested concentrations. Among these species the highest attention was focused onto detection of cadmium and nitrite ions, for which the detection limits, DL, estimated by 3σ method were found 0.0013 mg/L and 0.21 mg/L respectively, and these values are lower than the corresponding WHO guideline values of 0.003 mg/L (Cd2+) and 2 mg/L (NO2). The suitability of the developed sensors implemented with familiar devices for signal acquisition (Light Emitting Diode, LED, as light source and a digital camera as a signal detector), and chemometric methods for data treatment to perform fast and low-cost monitoring of species under interest, in real samples of environmental importance, is demonstrated.